DEVELOPMENT OF A METHOD FOR PRODUCING A QUALITY SEED PRODUCT BY LEAVING THE ONION IN PLACE IN THE TASHKENT REGION OF UZBEKISTAN - R. Nizomov, Sh. Makhamadaminov (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents the results of experiments on the development of a new resource-saving method of growing Istikbol onion seeds by leaving the bulbs in place and planting the seeds and obtaining high-quality seeds. According to studies, due to the fact that the physiological processes in the onion heads did not stop, and the root system was developed compared to the control, the appearance of bulbs, the flowering day and the seed ripening period were extended by 20-34 days more than the control, due to which the yield on August 30 was 532 kg, on September 9 - 515 kg, and on September 19 - 491 kg, the yield was higher by 14.2-23.7% compared to the control variety.